2007
DOI: 10.1038/sj.embor.7401135
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐sensitive reaction intermediate of F1‐ATPase

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. This license does not permit commercial exploitation or the creation of derivative works without specific permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
61
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 21 publications
10
61
1
Order By: Relevance
“…Single Molecule Rotation Assays-Single molecule rotation of TA2F 1 ␥2c was measured as described previously using either a ϳ200-nm magnetic bead duplex (high load probe) or a 40-nm gold nanoparticle (low load probe) (33,44,55,78). Briefly, a flow cell was constructed using a Ni 2ϩ -NTA-modified glass surface and an uncoated cover glass (Matsunami Glass Ltd., Japan), and biotinylated TA2F 1 ␥2c subunit complexes were immobilized on the Ni 2ϩ -NTA surface via a hexahistidine tag introduced at the N terminus of the ␤-subunit.…”
Section: Methodsmentioning
confidence: 99%
“…Single Molecule Rotation Assays-Single molecule rotation of TA2F 1 ␥2c was measured as described previously using either a ϳ200-nm magnetic bead duplex (high load probe) or a 40-nm gold nanoparticle (low load probe) (33,44,55,78). Briefly, a flow cell was constructed using a Ni 2ϩ -NTA-modified glass surface and an uncoated cover glass (Matsunami Glass Ltd., Japan), and biotinylated TA2F 1 ␥2c subunit complexes were immobilized on the Ni 2ϩ -NTA surface via a hexahistidine tag introduced at the N terminus of the ␤-subunit.…”
Section: Methodsmentioning
confidence: 99%
“…3C) transitions, the transition timings between state I and state II are affected only slightly by the concentration changes of the substrates. It has been shown that the angular position of ATP binding, ADP release, and P i release are around 0°, 0°(or somewhere between 0°and 80°), and 80°, respectively (4,6,24). Taking into account this rotation scheme, it seems that the transition between state III and state I is caused by binding/release of ATP/ADP and the transition between state II to state III is governed by P i release/binding.…”
Section: Magnetic Field Rotationmentioning
confidence: 99%
“…Dwells before the 80°and 40°substeps are termed the binding dwell and catalytic dwell, respectively. ADP release and P i release occur before (or during) the 80°and 40°substeps, respectively (47,48). States in catalytic dwell (D-F) correspond to the crystal structures of F 1 (51).…”
Section: Mechanism Of Inhibition Of Atp Synthesis By the C-terminalmentioning
confidence: 99%